Efektivitas Peraturan Nagari Suayan Nomor 3 Tahun 2016 Pasal 8 tentang Pemberlakuan Jam Malam bagi Remaja Menurut Fiqh Siyasah Tanfidziyah - Yoni Yolanda; Helfi Helfi (Lembaga Yasin AlSys, 2026)
Although Nagari Suayan Regulation Number 3 of 2016 Article 8 concerning curfew restrictions for adolescents has been implemented to maintain public morality and security, violations are still found in practice due to resistance from adolescents who feel that their freedom is restricted, as well as limited resources and the limited capacity of officials to conduct optimal supervision. This study aims to analyze the effectiveness of the implementation of Nagari Suayan Regulation Number 3 of 2016 Article 8 concerning curfews for adolescents and to review it from the perspective of Fiqh Siyasah Tanfidziyah. This study used field research with a descriptive qualitative approach. Primary data were collected through direct observation and in-depth interviews with the Nagari Head, nagari officials, and local community leaders. The results showed that, in terms of substance and legal foundation, this regulation was considered appropriate and aligned with the principles of Fiqh Siyasah Tanfidziyah because it is oriented toward public benefit and the protection of the younger generation from various potential dangers. However, the effectiveness of its implementation still needs to be improved because socialization has not been optimal and rule enforcement has not been carried out firmly. The conclusion of this study affirms that Nagari Suayan Regulation Number 3 of 2016 Article 8 has a relevant normative basis and socio-religious purpose, but it requires stronger implementation so that the objective of controlling curfews for adolescents can be achieved optimally. These findings imply the importance of improving socialization, supervision, and consistency in rule enforcement by the nagari government in realizing social order based on public benefit.